Pengembangan Kurikulum Merdeka untuk Meningkatkan Kualitas Pembelajaran - Heni Susanti; Mulyawan, Hafid; Nanang Purnama, Radik; Aulia, Maulida; Kartika, Ika (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Developing a curriculum that is in accordance with the times is one of the efforts made to improve the quality of education. The education system is expected to realize students to be able to have the ability to think critically, solve problems, be creative, innovative, communication skills, collaboration skills, search skills, management skills, skills to convey information and skills to use information and technology needed today. Based on the policy of the Indonesian Minister of Education and Culture, the Independent Curriculum is expected to create a happy learning atmosphere for both teachers and students. The method used in this research is qualitative through literature, namely by tracing the sources of writing that have been made previously to solve the problems discussed in a study. The results of this study indicate that in curriculum development, educators play an important role. The professionalism of educators when teaching in class is one of the things that can show the increasing quality of learning with the curriculum development used.